2018
DOI: 10.21315/jcdc2017.22.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Industrialized Building System (IBS) Provision in Local and International Standard Form of Contracts

Abstract: Industrialized Building System (IBS) has been introduced for over 40 years in Malaysia, with well-documented benefits and strong support from the government. Unfortunately, the pace of IBS adaptation is still slow and below the government's target. Construction players are still facing various issues and challenges when adopting IBS, particularly on contractual and procurement aspects, thus, it contributes to the low adoption of IBS in Malaysia. As of to date, there is still the lack of provisions in Malaysian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Next is the findings from (Mohd Fateh et al, 2016), preliminary survey (Stage 2), the critical inputs are findings from the respondents on perceptions of the current issues and the nature of the industry. Then in the findings from (Mohd Fateh & Mohammad, 2017), document analysis (Stage 3), the critical inputs are the significant clauses in relation to IBS construction after comparing seven (7) standard forms of contract and the understanding of the important factors for each significant clauses. Moving on to the findings from (Mohd Fateh & Nijar, 2019) questionnaire survey (Stage 4), the critical inputs are the findings from the respondents regarding the frequency and percentages analysis on the significant clauses and the findings from the Kruskal-Walis test whether there are differences of opinion between the three (3) groups (private clients, government and contractors).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next is the findings from (Mohd Fateh et al, 2016), preliminary survey (Stage 2), the critical inputs are findings from the respondents on perceptions of the current issues and the nature of the industry. Then in the findings from (Mohd Fateh & Mohammad, 2017), document analysis (Stage 3), the critical inputs are the significant clauses in relation to IBS construction after comparing seven (7) standard forms of contract and the understanding of the important factors for each significant clauses. Moving on to the findings from (Mohd Fateh & Nijar, 2019) questionnaire survey (Stage 4), the critical inputs are the findings from the respondents regarding the frequency and percentages analysis on the significant clauses and the findings from the Kruskal-Walis test whether there are differences of opinion between the three (3) groups (private clients, government and contractors).…”
Section: Methodsmentioning
confidence: 99%
“…IBS construction is able to offer huge benefits as reported by CIDB (2015a), but Malaysia still has a low take-up rate of Industrialised Building Systems (IBS) in construction. A number of reports (Mohd Fateh et al, 2016;Mohd Fateh & Mohammad, 2017;Mohd Fateh & Nijar, 2019) stated that the adoption for the IBS construction approach is relatively low due to lack of provision in the significant clauses in the standard form of contract for the IBS construction approach in Malaysia. From this scenario, it provokes this research to be conducted in line with findings from the literature reviews and Construction Industry Transformation Programme (CITP) as reported by (Construction Industry Development Board (CIDB), 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Fragmentation arise due to the isolation of professionals and lack of cooperation between construction parties (Mohd Fateh & Mohammad 2017). This siloed operation may gives rise to conflict which lend a negative impact to the quality of the design process and design outcome.…”
Section: Fragmentationmentioning
confidence: 99%
“…The 'over the wall' syndrome (Mohd Fateh & Mohammad 2017;Ojoko et al 2018) suggested that parties are only interested to transfer the risk to next parties as work completed. There is no knowledge sharing or learning process between the parties.…”
Section: Lack Of Knowledgementioning
confidence: 99%
See 1 more Smart Citation